The Grid: An Application of the Semantic Web. - Goble, C; Roure, D (2002)
The Grid is an emerging platform to support on-demand "virtual organisations" for coordinated resource sharing and problem solving on a global scale. The application thrust is large-scale scientific endeavour, and the scale and complexity of scientific data presents challenges for databases. The Grid is beginning to exploit technologies developed for Web Services and to realise its potential it also stands to benefit from Semantic Web technologies; conversely, the Grid and its scientific users provide application pull which will benefit the Semantic Web.